Caribbean Report 17-01-1992 - Crosskill, Hugh (anchor); Charles, Eugenia (interviewee); Gonzales, Anthony (interviewee); Islam, Shada (correspondent); Brenner, Phillip (interviewee) (The British Broadcasting Corporation, 1992)
In this report Sir Shridath Ramphal's criticism of CARICOM is condemned by Dominica's Prime Minister, Eugenia Charles, and the decline in trade among CARICOM states is also reported on. There are reports on an OAS sponsored meeting which attempts to restore ousted President Jean-Bertrand Aristide to office. In the final segments, the position of the European Community Executive Commission's stance on the expulsion of Haiti from the Lomé Convention is reported on and on the new foreign policy of the Cuban government.
1. Headlines (00:00-00:49)
2. Report on Dominica's Prime Minister, Dame Eugenia Charles condemnation of the criticism of the CARICOM leaders by the West Indian Commission chairman Sir Shridath Ramphal (00:50-01:30)
3. Interview with Eugenia Charles on her opinion of Shridath Ramphal's views and of CARICOM (01:31-06:00)
4. Report on the slump in trade between CARICOM states (06:01-06:34)
Keywords: Cuba -- Foreign relations -- United States.; Lomé Convention -- (1975).; Aristide, Jean-Bertrand.; Caribbean Area -- Commerce.; West Indian Commission.; Ramphal, S. S.; Caribbean Community.; Prime mnisters -- Dominica.; Castro, Fidel.; Charles, Eugenia.; CARICOM -- Trade.; Lomé Convention -- Haiti.